The Effects of Participant Motivational Behavioural Intention: The MARBLE Case - Yilmaz Akgunduz; Ovunc Bardakoglu; Yesim Koba (Tourism & Management Studies)
This study investigates the motivational factors underlying participation in trade fairs, and their effects on participant satisfaction and behavioural intentions. Data were collected through a questionnaire to 608 participants, selected by convenience sampling, at the International Natural Stone and Technologies Fair (MARBLE), held on 22-25 March 2017 in ?zmir, Turkey. Confirmatory factor analysis (CFA) was used to verify the convergent and discriminant validity of the scales while multiple regression analyses were used to test the research hypotheses. The results indicate that the trade fair participants were motivated by commercial attractiveness, financial attractiveness, information search, and city attractiveness. Participant satisfaction was significantly influenced by commercial attractiveness, financial attractiveness, and information search while behavioural intentions were determined by city attractiveness and information search.